The effect of local release antibiotic beads on in-vitro bacterial growth from tissue taken from infected diabetic foot ulcers. Issue Volume 1(2019)Issue A (8th March 2019) - Fletcher, Julie; Porter, Robert; Aiken, Sean; Delury, Craig; Michell, Stephen
Abstract : Diabetic foot infection is the main reason for diabetes-related hospitalisation and is a major cause of diabetes-related amputation. Recent figures published by Public Health England show that there are more than 163 diabetes related amputations in England every week. This study investigates the effect of antibiotic loaded calcium sulfate (Stimulan ® Rapid Cure) beads on in-vitro bacterial growth from tissue taken from diabetic foot infections. Patients were recruited from the Macleod Diabetes and Endocrine Centre at the Royal Devon and Exeter Hospital. Inclusion in the study was based on clinical recognition of an infected foot ulcer requiring wound debridement. Debrided tissue was homogenised and 50 µl spread over the surface of Columbia blood agar and fastidious anaerobe agar. Three replicate calcium sulfate beads containing a combination of vancomycin and gentamicin were then placed on the surface of the agar. Each bead contained approximately 3.4 mg and 1.6 mg of vancomycin and gentamicin respectively. Plates were incubated aerobically or anaerobically as appropriate. Zones of inhibition were recorded at 1 and 4 days. Calcium sulfate beads containing vancomycin and gentamicin were able to inhibit bacterial growth in all tissue homogenates tested with zone diameters ranging from 16 to 40 mm. Local release of antibiotics could have the benefit of achieving high local concentrations within poorly vascularised tissue which may inhibit bacterial growth at the wound site. By improving treatment of diabetic foot infections, it may be possible to prevent amputation, maintain mobility and conserve quality of life.